Analisis Perilaku Konsumen berdasarkan Theory of Planned Behavior: Studi Minat Beli Ulang pada Kopi Kenangan Jabodetabek - Muhammad Ananda Putra; Galuh Mira Saktiana (Journal of Management and Social Sciences, 2026)
This study aims to examine the effect of brand image and service quality on repurchase intention through customer satisfaction among Kopi Kenangan consumers in the Jabodetabek area. The research is based on the Theory of Planned Behavior (TPB), which explains that consumers' behavioral intentions are influenced by their attitudes and evaluations of products and services. The rapid growth of the modern coffee shop industry has intensified market competition, making it increasingly important for companies to maintain a strong brand image, deliver high-quality services, and ensure customer satisfaction to encourage repeat purchases. This study employs a quantitative approach using a purposive sampling technique involving 200 respondents who had purchased Kopi Kenangan products at least twice within the last three months. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that brand image and service quality have positive and significant effects on customer satisfaction and repurchase intention. Furthermore, customer satisfaction positively influences repurchase intention and serves as a significant partial mediator in the relationship between brand image, service quality, and repurchase intention. These findings emphasize the importance of enhancing customer satisfaction to strengthen long-term consumer loyalty.